International and comparative criminal justice and urban governance: convergence and divergence in global, national and local settings - Crawford, Adam (Cambridge Univ. Press, 2011)
"Criminal justice has traditionally been associated with the nation state, its legitimacy and its authority. The growing internationalisation of crime control raises crucial and complex questions about the future shape of justice and urban governance as these are experienced at local, national and international realms. The emergence of new international justice institutions such as the International Criminal Court, the greater movement of people and goods across national borders and the transfer of criminal justice policies between different jurisdictions all present novel challenges to criminal justice systems as well as our understandings of criminal justice. This volume of essays explores the implications and impact of criminal justice developments in an increasingly globalised world. It offers cutting-edge conceptual contributions from leading international commentators organised around the themes of international criminal justice institutions and practices; comparative penal policies; and international and comparative urban governance and crime control"--